Evaluating the State of Health Care Institutions: The Case of Lithuanian Municipalities - Breimerytė, Vaida; Kėdaitis, Vytautas; Miškinis, Algirdas; Trainavičius, Kęstutis (Ekonomika, 2019)
[full article and abstract in English]Huge differences between the territories that are divided into the city and district municipalities are found after examining theoretical and methodological literature, obtaining abundant statistical information on the status of health care institutions in Lithuania, disclosing the system of indicators describing that status, and taking into account the analysis of the data of all the statistic residents of the Territorial Health Insurance Funds (THIF) and those registered at the outpatient primary personal health care institutions (OPPHCI). The number of residents who have registered at the OPPHCI of city municipalities is different from the rates provided by the statistics. Therefore, in the calculation of health indicators, a meaningful selection of them will more accurately reflect the status of health care facilities. Of these indicators, it is important to select not only those that best describe the existing medical care level in the municipalities but those that are also informative. The system of indicators was selected on the basis of the Delphi method. This article analyzes the state of the health care institutions in Lithuania and the qualitative and quantitative indicators of health care and their evaluation at the municipal level. The authors of this article used multivariate statistical methods in evaluating the state of health care institutions. The reliability and the validity of the obtained results are verified by two models; thus, the stability and suitability of the models are tested in investigating the state of health care institutions in Lithuania. The final aim of the study is to evaluate the administrative units of different territories and, from the medical level perspective, identify the best performing and most lagging municipalities.
Keywords: health care institutions; composite indicator; factor analysis; principal component analysis